Digging up the un/romantic past: Reworking Popular Romance Codes in Rose Tremain’s "The Colour" and Maxine Alterio’s "Ribbons of Grace" - Fresno-Calleja, Paloma (Complutense Journal of English Studies, 2018)
This article offers a comparative reading of two neo-historical novels: Rose Tremain’s The Colour and Maxine Alterio’s Ribbons of Grace, both set in 19th century New Zealand and portraying interracial love stories between British and Chinese characters in the context of the gold rush. I read these neo-historical novels in relation to the romantic conventions they simultaneously employ and subvert. My contention is that their manipulation of certain romantic narrative and thematic conventions demonstrates the porosity between the literary and the popular ends of the historical spectrum. My analysis concentrates on how each author employs the romantic material to articulate their respective political agendas. Whereas Tremain’s novel prioritises a feminist perspective and emphasises the individual dimension of the love story, Alterio’s work is more concerned with the postcolonial revision of New Zealand’s past and highlights the social consequences of the interracial liaison.